Microbiota dynamic communities in sweet orange infected by “huanglongbing” in Iran - Shiva SAFARPOUR KAPOURCHALI; Mojdeh MALEKI; Ali ALIZADEH ALIABADI; Saeideh RAJAEE; Mohammad MEHDI FAGHIHI; Mehdi NASR ESFAHANI (Phytopathologia Mediterranea)
“Huanglongbing”-(HLB) or citrus-greening is one of the most serious citrus diseases worldwide. This study aimed to investigate the bacterial-communities associated with HLB-symptomatic sweet orange trees (Citrus sinensis) from different geographical regions in southern Iran. The 16S rRNA gene amplicon metagenomics sequencing of DNA extracted from the midrib and petiole tissues of symptomatic plants confirmed that the ‘Candidatus Liberibacter asiaticus’, was spread along the citrus-plantation regions in southern Iran, including Kerman, Sistan and Baluchistan, Fars, Hormozgan, and Khuzestan Provinces. The frequency of Operational Taxonomic Units (OTUs) related to ‘Ca. L. asiaticus’ was remarkable in the HLB symptomatic tree in the Fars region. No OTUs of ‘Ca. Liberibacter’ or ‘Ca. Phytoplasma’ were detected in the asymptomatic samples in the Kerman region. However, in asymptomatic materials representatives of the class Bacilli, including Lactobacillus spp. and Bacillus spp., showed 12- and 4-fold presence compared to the symptomatic samples of Kerman groves. Furthermore, the presence of OTUs belonging to ‘Ca. L. europaeus’ and ‘Ca. Phytoplasma aurantifolia’ was detected in sweet oranges. The simultaneous occurrence of ‘Ca. L. asiaticus’, ‘Ca. L. europaeus’, and ‘Ca. P. aurantifolia’ in HLB symptomatic orange trees in the Fars groves provided worthwhile insights for further research, although their epidemiological role in co-infections remains unknown. Microbial dataset in relation to variables associated with the plant health, defense, and disease helps to understand how these variables shape the citrus microbial community and identify individual that play a role in HLB suppression or promotion.